Demography, fishery yield and potential management strategies of painted spiny lobster (Panulirus versicolor) at Northwest Island, Great Barrier Reef, Australia - Frisch, A.; Hobbs, Jean-Paul (CSIRO Publishing, 2012)
Quantification of demographic parameters is important for understanding how populations interact with their environment and for developing sustainable harvest strategies. Our aims were to quantify demographic parameters and yield of painted spiny lobster (Panulirus versicolor) at Northwest Island, Great Barrier Reef and review fishery management regulations in view of the findings. Using catch-curve analysis and an intensive mark–recapture program, the local lobster population was found to be sparsely distributed (~1.3 ha–1), with low rates of natural mortality (0.25–0.28 year–1) and immigration (0.05 ha–1 year–1). Under current management regulations (no minimum size limit; MSL), yield-per-recruit peaked at 0.38 kg when fishing mortality was 0.4 year–1. Implementation of a 100-mm (carapace length) MSL is recommended because it provides the best compromise between yield and stock size and has minimal impact on existing fishing practices. Revocation of the prohibition on possessing egg-bearing females is also recommended because it would reduce wastage of lobsters that are inadvertently killed by spear-fishers and because there appears to be little chance of localised recruitment overfishing. This study provides the first estimate of mortality rate for P. versicolor and highlights the importance of this parameter for understanding demographic processes and optimising management regulations.